DEVELOPMENT OF BIOGRAPHY TEXT WRITING TEACHING MATERIALS ASSISTED BY WEEBLY MEDIA FOR GRADE X STUDENT - Dhifa; Nurita Bayu Kusmayati; Hestiyani Parai (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This research aims to develop biography text writing teaching materials assisted by Weebly media for Grade X students. The study employs a Research and Development (R&D) method using the ADDIE model (Analyze-Design-Development-Implementation-Evaluation). The sample consists of 37 Grade X students from SMA Diponegoro 1 Jakarta. Data were collected through interviews, needs analysis questionnaires, material and media expert validation results, as well as teacher and student assessments. Data analysis was conducted qualitatively and quantitatively. The results indicate that the development of biography text writing teaching materials assisted by Weebly media has been successfully carried out. The quality of the materials and media received ratings from material experts at 85.2% and media experts at 94%, both categorized as very good/very feasible. This research successfully developed systematic teaching materials to improve students’ biography text writing skills and received very good assessments from both material and media experts, making it suitable for implementation in learning.